2020
DOI: 10.1111/pan.13964
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of pediatric patients undergoing intrathecal nusinersen administration for treatment of spinal muscular atrophy: A single‐center experience

Abstract: Background Spinal muscular atrophy is a group of autosomal recessive inherited neurological disorders secondary to a genetic mutation that leads to progressive muscle weakness and atrophy. Recently approved by the Food and Drug Administration, Nusinersen is the first treatment specifically for spinal muscular atrophy. This drug must be administered intrathecally, as it does not cross the blood‐brain barrier. Aims Retrospective review of the individualized perioperative care of spinal muscular atrophy type I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…In several studies that have examined the clinical experience of nusinersen administration in SMA children, data about AEs are lacking or rough. 15,17,18,41 Bielsky et al 17 claimed there was not evidence of AEs in eight children with SMA type 2 undergoing general anesthesia using sevoflurane, nitrous oxide, and propofol for 61 LPs. However, AEs were not defined in the materials and methods section, so minor or minimal self-limiting AEs could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies that have examined the clinical experience of nusinersen administration in SMA children, data about AEs are lacking or rough. 15,17,18,41 Bielsky et al 17 claimed there was not evidence of AEs in eight children with SMA type 2 undergoing general anesthesia using sevoflurane, nitrous oxide, and propofol for 61 LPs. However, AEs were not defined in the materials and methods section, so minor or minimal self-limiting AEs could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…they mostly used non-pharmacological methods. 9 Either because the provider was inexperienced and the paediatric patient declined to be immobile or because intrathecal injection was scheduled to be done using another procedure, general anaesthesia using sevoflurane was administered to three of these five patients. The authors also reported that, after repeated nusinersen injections, two of the SMA I patients became stronger, and their anaesthetic plan was changed to using anaesthetic medication rather than local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Sever's work adds to a growing body of literature describing the safety and efficacy of general anaesthesia and procedural sedation in these complex patients undergoing routine nusinersen administration. 3,5 The authors did not report any postoperative complications in this cohort during the first 24 h; however, the majority of postoperative complications occur in the first 1-3 days after a procedure, 6 and many studies use a 30-day benchmark when assessing postoperative mortality and rate of adverse events. Furthermore, how are these patients faring for longer, higher risk surgeries?…”
mentioning
confidence: 91%